Stock market prediction using Kohonen network [electronic resource] - 193081 Teh, Eng Lee (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2005